Assessment of prevalence of domestic violence and mental health profile of adolescents exposed to domestic violence in an urban slum in Mumbai - Hiremath, Renuka C.; Debaje, Samadhan Prakashrao (International Journal of Research in Medical Sciences, 2017)
Background: Domestic violence in adolescent age group with prevalence of 22.5% is a major cause for causing depression and other behavioral changes. These changes caused due to domestic violence in adolescent age group may persist or worsen in later life as adult resulting in substance abuse or criminal mentality or depression or phobias. Purpose of current study was to assess the prevalence of domestic violence among the adolescents and to compare the mental health in terms of behavior, self-identity & depression among those with and without domestic violence and assessment of the contributory factors fueling domestic violence in the family. Methods: The study was conducted in Cheetah camp, an urban slum of Mumbai during Jan-March, 13. Study population includes subjects aged from 15-19 years fulfilling inclusion/exclusion criteria, a sample size of 74 (99% CL) was derived, using EPI Info software. Subjects were selected by random sampling & 7 households were visited for data collection from each sector. Scales such as AAMR-ABS, Hamilton depression scale and memory recall of the subjects were used in the study. Results: The prevalence of domestic violence in adolescence in cheetah camp urban slum was found to be 38.15% with various reasons. As the maladaptive behavior in the adolescent population increased the emotional violence against them also increased and was found to be statistically significant. Conclusions: Domestic violence is a major causal factor for causing depression of varying degree from mild to severe in adolescents. This depression or behavioural changes occurred during adolescent age group may persist life long and affects their life as adult resulting in failure for social and economic growth of them and of their family.